Fluorinated azobenzenes for shape-persistent liquid crystal polymer networks - Iamsaard, S; Anger, E; Asshoff, S; Depauw, A; Fletcher, S; Katsonin, N (Wiley, 2016)
Liquid crystal polymer networks respond with anisotropic deformation to a range of external stimuli. When doped with molecular photo-switches, these networks undergo complex shape modification under illumination. As the deformations reverse when irradiation stops, applications where thermal stability of the activated shape is required were precluded. Previous attempts to incorporate molecular switches with thermally stable photo-isomers were unsuccessful at photo-generating macroscopic shapes that are retained in time. Here, we show that the key to preserving photo-activated molecular deformation on the macroscopic scale is not only to engineer the thermal stability of the photo-switch but also to adjust the cross-linking density in the polymer network and to optimize the molecular orientations in the material. Our strategy resulted in materials containing fluorinated azobenzenes that retain photochemical shape morphing for more than eight days, which constitutes the first demonstration of long-lived photomechanical deformation in liquid crystal polymer networks.